Leadership development: an applied comparison of Gibbs' Reflective Cycle and Scharmer's Theory U. Issue 6 (7th September 2015) - Potter, Christopher
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine two contrasting leadership development methodologies, Reflective Practice and Scharmer's Theory U. Design/methodology/approach – Gibbs' Reflective Cycle and Scharmer's Reflecting Deeply exercise were applied to the same leadership incident on separate days. Findings – Reflective Practice provided helpful insights through focusing on one's thoughts, feelings and motives during the event, as well as the actions of others and the author's responses to them. The author found that using Scharmer's Reflecting Deeply exercise enabled a deeper understanding of the incident to emerge, which also provided new and distinct insights. Research limitations/implications – The main limitation was the case study nature of this exercise; these findings are merely the result of one person's experiences. Practical implications – To develop rounded leadership skills, leaders can benefit from tapping into all of their resources; these two approaches allow different aspects of one's intelligence to be accessed, which ought to facilitate greater development. Social implications – Many authors cite a current crisis of leadership, not least of all a perceived failure to tackle the environmental challenges we face. By seeking to develop more intelligent and rounded leaders, leadership itself ought to improve which in turn should help society tackle pressing issues. Originality/value – To the author's knowledge, a direct comparison of the leadership development methodologies used in this paper has not been previously described. This paper provides useful insights into the practical application of Reflective Practice and Scharmer's Theory U, which will help inform others seeking to develop as leaders.